Investigation of the Thermosyphon Performance for Different Working Fluids / Muhammad Fairuz Remeli ... [et al.] - Remeli, Muhammad Fairuz; Rosli, Mohd Arif Fikri; Bhathal Singh, Baljit Singh (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This study investigated a thermosyphon performance using different types of working fluids. Gravity assisted heat pipe of 15mm diameter, and 300 mm long with a thermal capacity of 240W was designed, fabricated and tested. An experimental setup was built to test the thermosyphon performance. For each performance test, the thermosyphon was filled with different working fluids including water, methanol and acetone. The thermosyphon was filled with 30% of working fluid fill ratio. The temperature distribution along the heat pipe was measured and recorded using thermocouples. The thermosyphon performance was evaluated based on the value of the heat transfer coefficient and the thermal resistances. At 30% fill ratio, the acetone had transferred the largest heat with 61.59 W.